4TH ALL-RUSSIA CONFERENCE "CONTRADICTIONS OF THE MODERN CARDIOLOGY: CONTROVERSIAL AND OPEN QUESTIONS" AND 3RD FORUM OF THE YOUNG CARDIOLOGISTS, 16-17 NOVEMBER 2015, SAMARA (Столичная издательская компания, 2015)
Information letter.